COMPARATIVE RESEARCH OF SURGICAL AND CONSERVATIVE SPINAL CORD INJURY TREATMENT IN A BIHAR TERTIARY CARE HOSPITAL: ANALYTICAL, CASE-CONTROL AND PROSPECTIVE STUDY - Kumar, Rajeev; Akash, Anant; Roshan, Reetesh (Student's Journal of Health Research Africa, 2024)
Background Spinal cord injuries (SCI) pose a substantial clinical challenge due to their complex nature and profound impact on patients' quality of life. Effective management strategies, including operative and conservative treatments, are crucial for improving patient outcomes. This study aims to compare the outcomes of operative versus conservative treatments in individuals with spinal cord injuries, focusing on functional recovery, complication rates, and overall patient outcomes. Methods A total of 300 participants were comprised, with 150 individuals in the operative treatment group and 150 in the conservative treatment group. Data were collected through clinical examinations and radiological evaluations. Patients were grouped based on the thoracolumbar injury severity score (TLISS). Functional outcomes were assessed using the ASIA impairment scale and Frankel grading system. Statistical analysis was done using SPSS version 23.0. Results The operative group showed significantly better functional outcomes, with a 26.7% improvement in ASIA scores and a 30% improvement in Frankel grades compared to 16.7% and 18.7%, respectively, in the conservative group. The recovery rate was faster in the operative group, with 36.7% recovering within three months compared to 20% in the conservative group. Complications were fewer in the operative group, with lower incidences of infection (6.7% vs. 13.3%), persistent pain (13.3% vs. 23.3%), and mortality (1.3% vs. 5.3%). Conclusion Operative treatment for spinal cord injuries offers superior benefits over conservative treatment, resulting in better functional outcomes, faster recovery rates, and fewer complications and mortality rates. These findings support the recommendation of operative intervention for suitable patients with SCI to optimize recovery and reduce adverse outcomes. Recommendations It is advised to conduct more studies with bigger sample sizes and a wider range of demographics to confirm these results and create thorough protocols for the treatment of spinal cord injuries.